PENGARUH PENERAPAN BAHASA JAWA KRAMA UNTUK MEMBENTUK KARAKTER SOPAN SANTUN SISWA AWWALIYAH DI MADIN AL-QOSIMI NAMPES NOGOSARI PANDAAN - Askhabul Kirom; Selvi Tri Agusti; Saifulah; Nanik Kholifah (Journal Multicultural of Islamic Education, 2022)
Humans can judge a person’s character just by looking at how they speck and how the language is used. Because anything that comes out of someone’s mount can indirectly reflect the character of a human being. Javanese Krama is a language that can be used to reflect humans into human beings who are polite and polite because in Javanese it has its own level which is used as a social order which is usually called uplaoad ungguh or andhap ashor, which is an attitude of humbling oneself politely and is a behavior that is polite and respect. Right that must be shown to everyone who is equal or higher. This research uses a quantitative approach to the correlation method. The data collection technique used a questionnaire of 30 questions with 5 altenative answer and documentation. The hypothesis of this study was analyzed using descriptive statistical data in the calculation of SPSS 25 for windows. The results of the study show that: 1) Shows that there is a significant influence between the application of Javanese Krama Language and the Polite Character of Awwaliyah Madin al-Qosimi Nampes Nogosari Pandaan Students. Seen from the result of the value of sig (0,000) < 0,05. 2) The magnitude of the influence of the application through the habituation method in the use of Javanese Krama Language with the character of student manners is very high, with proof that the person correlation value calculate with the SPSS 25 tool for windows with result reaching 0,984.